Constituents, Pharmacokinetics, and Pharmacology of Gegen-Qinlian Decoction - Jing-Ze Lu; Dan Ye; Bing-Liang Ma (Frontiers Media S.A., 2021)
Gegen-Qinlian decoction (GQD) is a classic traditional Chinese medicine (TCM) formula. It is composed of four TCMs, including Puerariae Lobatae Radix, Scutellariae Radix, Coptidis Rhizoma, and Glycyrrhizae Radix et Rhizoma Praeparata cum Melle. GQD is traditionally and clinically used to treat both the "external and internal symptoms" of diarrhea with fever. In this review, key words related to GQD were searched in the Web of Science, PubMed, China National Knowledge Infrastructure (CNKI), and other databases. Literature published mainly from 2000 to 2020 was screened and summarized. The main constituents of GQD could be classified into eight groups according to their structures: flavonoid C-glycosides, flavonoid O-glucuronides, benzylisoquinoline alkaloids, free flavonoids, flavonoid O-glycosides, coumarins, triterpenoid saponins, and others. The parent constituents of GQD that enter circulation mainly include puerarin and daidzein from Puerariae Lobatae Radix, baicalin and wogonoside from Scutellariae Radix, berberine and magnoflorine from Coptidis Rhizoma, as well as glycyrrhetinic acid and glycyrrhizic acid from Glycyrrhizae Radix et Rhizoma Praeparata cum Melle. GQD is effective against inflammatory intestinal diseases, including diarrhea, ulcerative colitis, and intestinal adverse reactions caused by chemotherapeutic agents. Moreover, GQD has significant effects on metabolic diseases, such as nonalcoholic fatty liver and type 2 diabetes. Furthermore, GQD can be used to treat lung injury. In brief, the main constituents, the pharmacokinetic and pharmacological profiles of GQD were summarized in this review. In addition, several issues of GQD including effective constituents, interactions between the constituents, pharmacokinetics, interaction potential with drugs and pharmacological effects were discussed, and related future researches were prospected in this review.